Analysis of Convergence Criteria in a Proposed Monetary Union: A Study of the Economic Community of West African States - SAKA, Jimoh Olakunle; ONAFOWOKAN, Ibiyemi Ajoke; ADEBAYO, Adekunle Ademayowa (International Journal of Economics and Financial Issues, 2014)
This study examines the processes of the monetary union of the Economic Community of West African States (ECOWAS). It takes a critical look at the convergence criteria and the various conditions under which they are to be met. Using the panel least square technique an estimate of the beta convergence was made for the period 2000-2008. The findings show that nearly all the explanatory variables have indirect effects on the income growth rate and that there tends to be convergence in income over time. The speed of adjustment estimated is 0.2% per year and the half-life is -346.92. Thus the economies can make up for half of the distance that separates them from their stationary state. From the findings, it was concluded that a well integrated economy could further the achievement of steady growth in these countries in the long run. Keywords: Monetary Union; Convergence Criteria; ECOWAS JEL Classifications: C23; E42; F33; F41